ASSESSMENT OF INDIGENOUS MICROORGANISM FOR NATURAL ATTENUATION OF ABANDONED MINE SITE - SRI HANDAYANI (Puslitbang tekMIRA, 2007)
Soil samples taken from an abandoned gold mine site in East Kalimantan exhibited high concentra- tion of manganese (9,830-13,190 mg/L), iron (340-8,060 mg/L) and arsenic (160-510 mg/L). However, the indigenous microbial population was found to be present at high level (> 107 CFU/g), indicated that the site matrix did not appear to be inhibitory and relatively favorable to microbial growth. Furthermore, laboratory microcosm studies showed that the indigenous microorganisms possessed a considerable bioremoval potential of contaminated metal at the site. Those results suggested that natural attenua- tion of metal bioremoval would occur under present site condition.